2014
DOI: 10.1167/iovs.14-14524
|View full text |Cite
|
Sign up to set email alerts
|

Axial Eye Growth and Refractive Error Development Can Be Modified by Exposing the Peripheral Retina to Relative Myopic or Hyperopic Defocus

Abstract: Eye growth and refractive state can be manipulated by altering peripheral retinal defocus. Imposing peripheral hyperopic defocus produces axial myopia, whereas peripheral myopic defocus produces axial hyperopia. The effects are smaller than using single-vision contact lenses that impose full-field defocus, but support the use of bifocal or multifocal contact lenses as an effective treatment for myopia control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
166
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 54 publications
7
166
0
2
Order By: Relevance
“…If it is possible to slow axial eye growth in myopes by manipulating the peripheral retinal image shell, then encouraging axial eye growth in hyperopes using the same rationale is plausible and is a notion supported in the literature by animal work [10].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…If it is possible to slow axial eye growth in myopes by manipulating the peripheral retinal image shell, then encouraging axial eye growth in hyperopes using the same rationale is plausible and is a notion supported in the literature by animal work [10].…”
Section: Discussionmentioning
confidence: 85%
“…Myopic eyes typically exhibit relative hyperopic blur in the periphery [7,8], which is thought to be a precursor to the development of myopia [9]. Studies on animals have suggested that manipulating peripheral defocus through optical means while simultaneously providing correct axial focus can either discourage or encourage axial eye growth to effectively treat myopia or hyperopia, respectively [10]. It has been established that progression of myopia and axial eye growth can be significantly reduced in children and adolescents through the use of bifocal or dual-focus contact lenses [11][12][13]; these contact lenses are designed to correct distance central myopia while simultaneously imposing myopic defocus.…”
Section: Introductionmentioning
confidence: 99%
“…Laties and colleagues once posited that the retina may participate in the postnatal regulation of eye growth to minimize refractive error [40,41]. Previous studies have shown that the axial overgrowth and myopia caused by visual form deprivation can be manipulated by altering peripheral retinal defocus [42]. In addition, early retinal changes are reflected in retinotopically specific plasticity, which can be assessed by visual cortical thickness [34,43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the literature provides evidence that the peripheral retina plays a role in the development of myopia, [17][18][19] but also that it is involved in visually induced postural control.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies involving current correction modalities, including methods for myopia control, also suggest that the peripheral retina may play a role in the development and progression of myopia. [17][18][19] In addition, the literature provides evidence that myopes and emmetropes possess intrinsic differences. 20 Knowing that the peripheral visual experience differs between myopes and emmetropes and that peripheral quality may potentially affect posture, it is reasonable to believe, as previously mentioned, that refractive error could therefore have an effect on postural control.…”
mentioning
confidence: 99%